The Essentiality of Sustainability and Variety for Industry Collaborations with University Partners - Wu, Hong (International Journal of Advanced Corporate Learning (iJAC), 2017)
The industrial assigned student projects is a good approach for to many engineering colleges. This approach provides students opportunities to research and learn the real world and business tasks. At Østfold University College of Norway, industry assigned student projects are crediting into the regular study curriculums and contribute greatly to the quality of teaching, appreciated by the students and industrial partners. We look at a statistics overview of the college´s bachelor projects over last 10 years, and examine the percentage and sustainable performance of industry assigned student projects. The analysis shows a trend that a sustainable collaboration with few large size industrial partners rather involved more than one student project over the past few years, while major part of the industrial partners, mainly small companies assigned only 1-2 projects then drop off, simply with a coming and go performance mechanism, not really sustainable. We question the performance sustainability of industrial assigned student projects and necessity of company contributions and engagement for teaching approach.